A Review of Angus Deaton's The Great Escape: Health, Wealth, and the Origins of Inequality - Weil, David N. (Journal of Economic Literature, 2015)
This book explores the relationship between the material standard of living and health, both across countries and over time. Above all, Deaton is interested in the question of whether income growth contributes significantly to better health. His answer is no: saving lives in poor countries is not expensive, and there are many episodes of massive health improvements in the absence of income growth. As an alternative, he argues that the cross-sectional correlation between health and income is induced by variation in institutional quality, while over time, parallel improvements in income and health have been a result of advancing knowledge. (JEL E23, I12, I14, I15, O15, O47)